Analysis of the effects of torsional impact tools on drill string stick–slip vibration - Chaoyi She; Jianhua Guo; Jie Wu; Qingsong Qiao; Beiqiao Meng; Yuting Zhang (Energy Exploration & Exploitation)
Torsional impactor is widely used in deep and ultra-deep wells because it can suppress stick–slip vibration and increase ROP. As the direct factor affecting torsional impactor effect, it's working parameters study is still not sufficient. In order to evaluate the effect of torsional impactor, considering the high-frequency torque provided by torsional impactor, a dynamic model of torsional vibration of drillstring is established, and by compiling the calculation program, and solved by The fourth–fifth Runge–Kutta, the influence of main working parameters of torsional impactor on stick–slip vibration is analyzed. The results show that: The torsion impacter can effectively reduce the stick–slip period of drillstring, thereby suppressing the stick–slip vibration and increasing the ROP; when the torsional impact load is low, increasing the torsional impact load can reduce the stick–slip period and even eliminate the stick–slip vibration, However, when the stick–slip disappears, increasing the torsional impact load has small effect on the torsional vibration. Increasing the impact frequency can suppress the stick–slip vibration and improve the stability of the drillstring during rotation. The results provide reference significance for the selection of working parameters of torsional impactor.